Digital Muslim Parenting and Generation Z Behaviour: A Systematic Literature Review for Islamic Religious Education Learning Design in Higher Education - Mahdi, Mahdi; Putra, Dody Dahwana; Rukhoyah, Rukhoyah; Mawarid, Habib Hazmy (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to explore the types of digital parenting styles adopted by Muslim parents, examine their influence on the social, moral, religious, and digital behaviors of Generation Z, and formulate implications for the design of Islamic Religious Education (PAI) in higher education. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 protocol to identify publications published between 2015 and 2024 across Scopus, Web of Science, Google Scholar, and Sinta. Of the 487 articles identified, 28 studies met the inclusion criteria and were analyzed in depth using thematic synthesis, whereby findings were coded, categorized, and synthesized into cross-cutting themes addressing the three research questions. The results identified three main typologies of digital parenting: authoritative Islamic digital parenting (50%), restrictive digital parenting (32%), and permissive digital parenting (18%) among the reviewed studies. Authoritative Islamic digital parenting was consistently associated with stronger indicators of moral reasoning and religiosity among Generation Z, as reflected in higher levels of ethical filtering, empathy, and religious engagement reported across the reviewed studies. The findings further indicated that digital parenting patterns were associated with social empathy, digital ethical resilience, religious engagement, digital literacy, and privacy management skills among Generation Z. Among the three typologies, authoritative Islamic digital parenting demonstrated the strongest potential for fostering positive digital character and behavior and serving as a protective factor. These findings highlight the need to redesign Islamic Religious Education by integrating Islamic digital competencies, social media fiqh, digital ethics, blended learning, project-based learning, and authentic digital portfolio-based assessment, thereby enhancing its relevance to the digital habitus of contemporary students.